Investigation of Bacteremia due to Aeromonas Species and Comparison with That due to Enterobacteria in Patients with Liver Cirrhosis - Toru Shizuma; Chiharu Tanaka; Hidezo Mori; Naoto Fukuyama (Gastroenterology Research and Practice)
Background. The role of Aeromonas species (sp.) in bacteremia in Japanese patients with liver cirrhosis is poorly understood. Aim. To establish the importance of Aeromonas sp. as a cause of bacteremia in patients with liver cirrhosis. Methods. Clinical and serological features and short-term prognosis were retrospectively investigated and compared in Japanese patients with bacteremia due to Aeromonas sp. (𝑛=11) and due to enterobacteria (E. coli, Klebsiella sp., and Enterobacter sp.) (𝑛=84). Results. There were no significant differences in patients’ clinical background, renal dysfunction, or short-term mortality rate between the two groups. However, in the Aeromonas group, the model for end-stage liver disease (MELD) score and Child-Pugh score were significantly higher than in the enterobacteria group. Conclusion. These results indicate that the severity of liver dysfunction in Aeromonas-induced bacteremia is greater than that in enterobacteria-induced bacteremia in Japanese patients with liver cirrhosis.